Pengaruh Profitabilitas, Likuiditas, dan Kebijakan Dividen Terhadap Nilai Perusahaan Pada Perusahaan Healthcare Di BEI - Nabilla, Tera Shalza; Dara, Siti Ruhana (STREAMING, 2022)
This study aims to determine the effect of profitability, liquidity, and dividend policy on firm value in healthcare sector companies listed on the Indonesia Stock Exchange for the 2017-2020 period. The sampling technique used purposive sampling and obtained a sample of 14 companies. This study uses quantitative methods with multiple regression analysis on panel data, namely classical assumption test, model feasibility test and hypothesis testing. The results show that: 1) profitability has no effect on firm value, 2) liquidity has no effect on firm value, 3) dividend policy affects firm value, 4) profitability, liquidity, and dividend policy simultaneously affect firm value.